The perception of text triggers reflexive oculomotor orienting. (September 2018) - Taub, Keren; Yuval-Greenberg, Shlomit
Abstract: As you read this text, your brain is busy integrating numerous different processes–perceptual, cognitive and motor. While you acquire the semantic and linguistic contents of this abstract, your eyes traverse its lines with speed and coordination. The oculomotor response to text is so rapid and precise that it is hypothesized it to be partially based on reflexive orienting mechanisms. In this study we examined the hypothesis that the presentation of written text triggers reflexive orienting toward the direction of reading, similarly to the effect of peripheral stimulation or that of symbolic directional cues (arrows or gazing eyes). In three experiments, participants (N = 120) were presented with task-irrelevant text, shortly followed by a left/right pro-saccade task. The first experiment confirmed the hypothesis by showing that saccades which are congruent with the direction of reading are faster than those which are incongruent. This was observed both in right-to-left (Hebrew) and in left-to-right (English) reading-systems and similarly in native-Hebrew and native-English readers. A second experiment showed that this directional bias is found not only for readable text but also for meaningless strings of letters. This confirmed that the bias is driven pre-reading non-lexical processes. The third experiment examined the time-course of this effect. We conclude that text-perception actives early reflexive eye-movements programs and suggest that this link is an essential building-block of fast and effortless reading.